Memoirs of a hamster - Scillian, Devin; Bowers, Tim (Ann Arbor, MI : Sleeping Bear Press, 2013)
"A pet hamster is enticed by the family cat to venture outside his well-equipped cage to the sunroom only to very quickly discover life outside his cage is not the best for him."--Provided by publisher.
Kirkus Review, April 2013
2.4
K-3
Keywords: Hamsters -- Juvenile fiction; Cats -- Juvenile fiction; Hamsters -- Fiction; Cats -- Fiction; Hamsters -- Fiction; Cats -- Fiction; Picture books for children